SCIENCE IN SOCCER : TRANSLATING THEORY INTO PRACTICE - Gregson, Warren; Littlewood, Martin (London : BLOOMSBURY SPORT, 2018)
Science in Soccer offers a series of contemporary insights into the multidisciplinary approach to delivering sports science support in elite level professional football.
Keywords: Sports sciences; Soccer